2009
DOI: 10.3858/emm.2009.41.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a chemical chaperone on genetic mutations in α-galactosidase A in Korean patients with Fabry disease

Abstract: Fabry disease is an X-linked inborn error of glycosphingolipid catabolism that results from mutations in the gene encoding the α-galactosidase A (GLA) enzyme. We have identified 15 distinct mutations in the GLA gene in 13 unrelated patients with classic Fabry disease and 2 unrelated patients with atypical Fabry disease. Two of the identified mutations were novel (i.e., the D231G missense mutation and the L268delfsX1 deletion mutation). This study evaluated the effects of the chemical chaperones 1-deoxygalacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…19 In this report, we found remarkably high residual enzyme activity of a protein with the p.E66Q mutation, previously known as a pathogenic mutation in patients with atypical Fabry disease. 9,11,17,20 p.E66Q synthesizes 40% of wild-type enzyme activity when overexpressed in COS-7 cells, indicating that p.E66Q might be a mild mutation or a functional single nucleotide polymorphism (SNP).…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…19 In this report, we found remarkably high residual enzyme activity of a protein with the p.E66Q mutation, previously known as a pathogenic mutation in patients with atypical Fabry disease. 9,11,17,20 p.E66Q synthesizes 40% of wild-type enzyme activity when overexpressed in COS-7 cells, indicating that p.E66Q might be a mild mutation or a functional single nucleotide polymorphism (SNP).…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, the enzyme activity of p.E66Q variant was 43.8±3.03% of normal activity in transiently overexpressed COS-7 cells (Table 2). Confocal microscopy showed that the p.E66Q variant GLA was expressed in lysosomes, a pattern similar to that of wild-type GLA, whereas the enzyme with the p.R112C mutation, a pathogenic mutation in atypical Fabry disease and that retains 4.7±0.13% of normal activity, 19 was not expressed in lysosomes, but was rather retained in the endoplasmic reticulum (ER) (Figure 1). Allele frequencies of the p.E66Q variant in the Korean population Among 1176 alleles tested, 12 were found to harbor the p.E66Q variant.…”
Section: Identification Of 25 Genotypes From 28 Korean Families With mentioning
confidence: 99%
See 3 more Smart Citations